Research of heat conductivity of quartz material - A.K. Хасенов; Г.A. Булкаировa; Б.Р. Нусупбеков; E.Р. Шрагер; Д.Ж. Карабековa; M.М. Болатбекова; Е.A. Жолдасбек (Қарағанды университетінің хабаршысы. Физика сериясы)
In the article the results of a study of heat conductivity and thermal resistance of quartz-containing materials were presented. The object of the study was a quartz mineral from the Aktas deposit, located in the Ulytau district of the Karaganda region. The initial size was a piece of quartz mineral measuring 5–10 mm, which was disassembled mechanically. To prepare the samples under study, quartz powder 0.2 mm thick, crushed by the electric pulse method, was used. Electropulse technology is one of the methods based on the influence of Yutkin, accompanied by the formation of a specially formed high-voltage pulsed electrical discharge inside a volume of liquid. The pulse discharge frequency of the electrohydropulse installation for grinding the mineral to the required fraction was f = 3 Hz, the pulse capacitor capacitance C = 0.4 μF, the pulse discharge voltage U = 18–37 kV. The samples under study were made in the following dimensions: width 100 mm, length 100 mm, height 25 mm. To evaluate the thermophysical properties of manufactured samples in a stationary mode, the ITP-МG4 “100” installation was used, which determines the heat conductivity and thermal resistance of materials for thermal insulation of industrial equipment and pipelines in accordance with GOST 7076, based on the thermoelectric method, and GOST 30256, based on the thermal probe method. As a result of the study, a graph of the temperature dependence of heat conductivity and thermal resistance of quartz-containing materials was obtained. Based on the results obtained, it was established that the thermophysical parameters of the sample containing quartz are lower compared to the sample consisting of cement.